FROM AUTHORITY TO INSTITUTIONAL TRUST; A STUDY OF KYAI MODALITIES IN PESANTREN COMMUNITIES - Agus Nu'man (PEDAGOGIK : JURNAL PENDIDIKAN, 2025)
Leadership plays a pivotal role in sustaining social cohesion within pesantren. The authority of kyai is not only rooted in personal qualities but also shaped by cultural legitimacy, genealogical heritage, and symbolic charisma that extend influence beyond educational boundaries into socio-political spheres. This study focuses on the role of the kyai as the highest authority holder who is not only responsible for the direction of education. Employing a qualitative approach, the study was conducted in two prominent pesantren in East Java. Data were collected through participant observation, in-depth interviews, and documentation. Findings reveal that kyai leadership builds trust through the synergy of economic independence, alumni-based social networks, preservation of cultural traditions, and symbolic authority manifested in rituals, rhetoric, and institutional symbols. The study concludes that public trust is not an instant achievement but a socially constructed process rooted in sustained moral conduct, adaptive leadership, and cultural continuity. This research contributes to the sociology of Islamic education by demonstrating how kyai transform personal authority into institutional legitimacy through interdependent modalities.